Perspektif Normatif pada Jurnalisme Digital - Mufti Nurlatifah; Billy Sarwono; dr. Irwansyah (Jurnal Media dan Komunikasi Indonesia, 2020)
Law perspective on communication studies provide normative point of view to analize phenomenon of communication. This point of view doesnt discuss rules of the game as the domain, but sees “what shoule be” as main focus. Normative theory provides causality to explain communication phenomena holistically. For journalism digital, normative theory have two main question to discuss. First, the position of digital journalism as current condition in communication studies. Second, the influence of digital journalism in democratic society. This conceptual study aims to answer both question and looking new horizon of normative theory among perspectives in the communication studies.